QUALITY OF COMMUNAL SERVICES – AS A FACTOR OF ECONOMIC DEVELOPMENT - Kiyomov Yusuf To'xtasin og'li; Shokhabbos Dolliyev (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses providing quality housing and communal services to the general public, implementing a unified state policy in the field of housing and communal services, network coordination, and monitoring the technical condition of multi-apartment houses, including the organization of perfect and current multi-apartment housing stock.